Optimizing Village Potential Through Kukerta Building Villages to Improve the Quality of Education, Health and Economy in Laksamana Village - Leli Deswita; Hazirah Febrina; Aulia Mawaddah; Zakaria Avandi; Alfiryani; Anugerah Permata Sari; Fathia Hanin Nabila; Sekar Puspita Ningrum; Eka Kurniawati; David Seand Rafael; Barzevan Limbong (Indonesian Journal of Advanced Social Works, 2023)
Kuliah Kerja Nyata (Kukerta) is one of the activities that must be carried out to apply the knowledge gained during lectures as well as a concrete form of community service. Kelurahan Laksamana is one of the Kelurahan in Kecamatan Dumai Kota, Dumai City. Kelurahan Laksamana which is the target Kelurahan in the 2023 Riau University kukerta activities. To help Laksamana develop more and create quality Human Resources, Riau University kukerta students try to help by holding literacy-themed activity programs and other work programs with socialization, training and teaching methods . In carrying out the service, the village and Laksamana community are very supportive and actively participate in all activities held by Kukerta students so that the objectives of the program are achieved.